Animals for Tools: The Origin and Development of Bone Technologies in China - Ma, Shuwen; Doyon, Luc (Frontiers in Earth Science, 2021)
The origin and development of bone technology in China are reviewed in the light of recent discoveries and compared to trends emerging from the European and African archaeological records. Three categories of osseous tools are targeted: (1) unmodified bone fragments bearing traces of use in technological activities; (2) bone fragments modified to a variable extent with techniques generally used in stone technologies; (3) osseous fragments entirely shaped with techniques fit for the manufacture of formal bone tools. Early evidence of bone technologies in China are sporadically found in contexts dated between 1.8–1.0 Ma. By the late MIS6–early MIS5, bone tools are well-integrated in the technological systems of Pleistocene populations and the rules guiding their use appear increasingly standardized. In addition, the first evidence for the use of osseous material in symbolic activities emerges in the archaeological record during this period. Finally, between 40–35 ka, new manufacturing techniques and products are introduced in Late Palaeolithic technological systems. It is first apparent in the manufacture of personal ornaments, and followed by the production and diversification of formal bone tools. By that time, population dynamics seem to become materialized in these items of material culture. Despite regional specificities, the cultural trajectories identified for the evolution of bone technologies in China seem entirely comparable to those observed in other regions of the world.